QUALITY OF LIFE PATIENT EPILEPSY: EXPLORING THE ROLE OF SOCIODEMOGRAPHIC AND CLINICAL FACTORS IN AN INDONESIAN COHORT - Permatasari, Desita; Rakhmi, Najmi Hidayatur; Dewi, Meilda Sartika (Journal of Pain, Headache and Vertigo, 2026)
Background: Epilepsy is a chronic neurological disorder characterized by recurrent seizures, with substantial impact not only on clinical outcomes but also on psychosocial and quality of life domains. Assessing quality of life (QoL) has become essential in evaluating treatment success, as it encompasses dimensions beyond seizure control. Objective: This study aimed to analyze the relationship between sociodemographic and clinical factors with QoL among epilepsy patients at the Neurology Polyclinic of Dr. Ansari Saleh Regional Hospital, Banjarmasin. Method: An observational analytic study with a cross-sectional design was [A2.1]conducted on 50 patients diagnosed with epilepsy. Consecutive sampling was applied. QoL was assessed using the Indonesian-validated version of the Quality of Life in Epilepsy Inventory-10 (QOLIE-10). Sociodemographic and clinical data were collected through interviews and medical records. Data were analyzed using the Shapiro-Wilk test for normality and one-way ANOVA for comparisons, with p<0.05 considered significant Results: ANOVA revealed no significant associations between QoL and age, sex, education, age at first seizure, duration of epilepsy, seizure duration, or EEG findings. However, medication adherence was significantly associated with QoL (p<0.001), and polytherapy showed a trend towards lower QoL compared with monotherapy (p=0.088). The findings emphasize that modifiable factors, particularly medication adherence, have greater influence on QoL than fixed sociodemographic or clinical variables. This suggests that patient education, psychosocial support, and adherence-focused interventions are crucial in improving QoL in epilepsy care. Conclusion: Medication adherence is the most important determinant of QoL among epilepsy patients in this setting. Clinical practice should prioritize strategies to enhance adherence, while future studies with larger and more diverse samples are needed to confirm these findings and explore psychological determinants.